Characteristics of PM2.5 Pollution in Osorno, Chile: Ion Chromatography and Meteorological Data Analyses - Ayane Nakamura; Nobutake Nakatani; Fumito Maruyama; So Fujiyoshi; Rodrigo Márquez-Reyes; Ricardo Fernández; Jun Noda (Atmosphere, 2022)
Over the decades, air pollution has become a serious problem in Osorno, Chile. This study aims to clarify the source of PM2.5 by comprehensively analyzing its chemical composition and comparing it with meteorological conditions. The PM2.5 and filter samples were collected during April 2019–August 2019 using a continuous particulate monitor. The analyses were conducted using Image J software, ion chromatography, and backward trajectory. The ion composition and the PM2.5 were compared. The results on the PM2.5 and potassium (K+) concentrations indicated a correlation factor of 0.93, indicating that biomass combustion, such as wood burning, is the dominant source of PM2.5 in Osorno. High PM2.5 concentrations of over 170 to 1124 µg/m3 were observed in low temperature, low precipitation, and low wind speed periods—meteorological conditions contributed to the development of a thermal inversion layer. In addition, correlations of 0.61 to 0.67 were found among the detected ions that are often found in seawater. The backward trajectory analyses showed dominant air mass transport from the South Pacific Ocean, suggesting that part of the detected PM2.5 was derived from the marine environment. Continuous monitoring and mitigation strategies focusing on wood combustion activities are necessary to alleviate the current air pollution problem in Osorno city.